Identification in multiscale thermoelastic problems - Długosz, Adam; Burczyński, Tadeusz (Computer Assisted Methods in Engineering and Science, 2013)
The paper deals with the identification in multiscale analysis of structures under thermal and mechanical loads. A two-scale model of porous materials is examined. Direct thermoelastic analyses with representative volume element (RVE) and finite element method (FEM) are taken into account. Identification of material constants of the microstructure and identification of the shape of the voids in the microstructure are considered. Identification functional is formulated on the basis of information obtained from measurements in mechanical and thermal fields. Evolutionary algorithm is used for the identification as the optimization technique. Numerical examples of identification for porous aluminum models are enclosed.